2009
DOI: 10.1093/aje/kwn413
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Effect of Vitamin E Supplementation on the Mortality of Male Smokers by Age and Dietary Vitamin C

Abstract: The Alpha-Tocopherol, Beta-Carotene Cancer Prevention (ATBC) Study (1985–1993) recruited 29,133 Finnish male cigarette smokers, finding that vitamin E supplementation had no overall effect on mortality. The authors of this paper found that the effect of vitamin E on respiratory infections in ATBC Study participants was modified by age, smoking, and dietary vitamin C intake; therefore, they examined whether the effect of vitamin E supplementation on mortality is modified by the same variables. During a median f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 34 publications
3
46
1
Order By: Relevance
“…Vitamin E had no influence on mortality among those who had dietary vitamin C intake less than the median. The modifying effect of vitamin C was not explained by other substances in fruit and vegetables (5). The interaction between vitamins C and E is well documented (6,7), and may explain the role of vitamin C as a modifying factor for some vitamin E effects.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Vitamin E had no influence on mortality among those who had dietary vitamin C intake less than the median. The modifying effect of vitamin C was not explained by other substances in fruit and vegetables (5). The interaction between vitamins C and E is well documented (6,7), and may explain the role of vitamin C as a modifying factor for some vitamin E effects.…”
mentioning
confidence: 87%
“…It is probable that the effects of vitamin E are modified by, for example, vitamin C as found in our study, but the effects seem to depend on the characteristics of population groups so that only the oldest people benefited (5, 10). Jiang et al (1) did not give any justification for dismissing the strong evidence of heterogeneity in the effects of low dose vitamin E on mortality (5,10).…”
mentioning
confidence: 99%
“…Actually, the effect of vitamin E supplementation on morbidity and mortality varies between different population groups. More careful evaluation by subject stratification of ATBC study data showed that vitamin E may either prevent or increase the overall risk of mortality depending on age and vitamin C intake [116]. More in detail, when the dietary vitamin C intake was above the median of 90 mg/day, vitamin E increased mortality among those aged 50-62 years by 19% and decreased mortality among those aged 66-69 years by 41%.…”
Section: Individual and Genetic Predictors Of Vitamin E Responsivenessmentioning
confidence: 99%
“…Clinical effect of vitamin E is not observed in recipients who consume less vitamin C containing diet [34]. It has been observed that vitamin E supplementation transiently increases the risk of active tuberculosis in heavy smokers if co-supplemented with vitamin C [35].…”
Section: Solution Of the Paradoxmentioning
confidence: 99%